Creating shared value in Rock in Rio business model: Case study - Ribeiro, T. D.; Ferreira, P. A.; Vaz, Maria João (2018 13th Iberian Conference on Information Systems and Technologies (CISTI), 2018)
This discourse will attempt to discuss `Creation of Shared Value' (CSV) through the case study of the music festival "Rock in Rio" (RIR) in order to further understand the company's sustainability program. The main goal is to clearly recognize if RIR uses a genuine practice of CSV to accomplish their social policies. To commence, we started with the State of Art, studying the CSV theory created by Porter and Kramer, as well as the authors that were either in support of, or against, the strategy. Qualitative Research Method was used, thus focusing the enterprise case study, by analysing media interviews given by the managerial staff of RIR. Content analysis was used to process data and deliver results. The main limitation of the study was the lack of institutional information, due to an absence of responses, to the survey in sufficient time by RIR's managers, subsequently a triangulation of the information acquired could not be achieved.